HPV vaccination strategies targeting hard-to-reach populations: - Bonner, Kimberly; Banura, Cecily; Basta, Nicole E. (ELSEVIER, 2017)
Highlights • High HPV vaccination coverage is critical for preventing cervical cancer worldwide. • School-based programs effectively deliver vaccines to adolescents attending school. • We propose ways to ensure out-of-school girls have equitable access to HPV vaccines. • Important to quantify out-of-school girls and research barriers to HPV vaccination. • To increase uptake, consider targeted communication, outreach and integrated programs.
Out-of-school girls in LMICs
Keywords: HPV; Human papillomavirus vaccine; Cervical cancer; Implementation; Vaccine uptake; Vaccination programs; Adolescents School-based programs; LMICs; Africa